Efficiency Economic Of Chainsaw and Timber Jack 450C Skidder Evaluation in Felling Operation and Ground-Base Skidding System - Azarnoush, Mohammadreza; Fathi, Jafar (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
In this research, an empirical time study was carried out, to estimate effects of a tree felling and skidding operations on time consumption, productivity rate, cost, and present a regression model of chainsaw and Timber jack 450C skidder. The study revealed that the hourly production of felling with and without delay times was 51.6 (9.5 trees/hr) and 86.2 (16 trees/hr) cubic meters per hour, respectively. The survey of total production of tree felling operation using a chainsaw showed that, increasing tree diameter increase total production rate without delay time as power model, similar to this production cost for one cubic meter is decreased. The average net and gross time, of a felling cycle was equal 3.74, 6.24 min per cycle, respectively. The total production rate with and without delay times in skidding with Timber jack 450C model skidder was 7.92 and 12.1 cubic meters per hour, respectively. The rate of machine 687.69 US$ per hour was estimated. The cost of skidding with and without delay times was 117.19 US$ and 76.64 US$ per cubic meter, respectively. Therefore, total delay times in skidding with Timber jack 450C model skidder were devoted to the two working cycles as follows: travel loaded and travel empty. The effects of all variables affecting on change of the time-consuming and skidding cost firmed that increasing all variables increase skidding cost as power model.